Optimized Automated Virtual Private Network Management System Utilizing WireGuard and Redis with Delta Processing on MikroTik RouterOS - Ardiansyah; Hartinah; Wahyuddin Saputra (Program Studi Teknik Komputer, 2025)
In the contemporary network infrastructures, the pursuit of secure, efficient, and easily manageable connectivity has become a fundamental design requirement. WireGuard, a next-generation Virtual Private Network (VPN) protocol, delivers superior cryptographic efficiency and operational performance compared to traditional protocols such as OpenVPN and IPsec. This study presents the development of an optimized automated VPN management framework built upon WireGuard and integrated into MikroTik RouterOS via a web-based control interface. The proposed system automates user registration, account approval, and configuration generation processes, thereby reducing administrative overhead and minimizing human-induced configuration errors. To further enhance system performance, an optimized traffic logging mechanism was implemented using the Redis in-memory database combined with a Delta Processing algorithm, which records only incremental traffic variations instead of cumulative totals. Experimental validation demonstrates that this integration reduces router CPU utilization by 30% and decreases logging latency by 40% relative to conventional polling-based methods. The results confirm that the proposed solution not only achieves full automation of VPN management but also significantly improves the responsiveness and scalability of real-time traffic monitoring. To the best of our knowledge, this research introduces the first Redis-based Delta Processing integration for VPN optimization on MikroTik platforms, offering a lightweight, scalable, and high-throughput solution for multiuser network environments.